"RAJIV GANDHI WATER MANAGEMENT MISSION'S ECONOMIC CONTRIBUTION TO RURAL AREAS" (WITH REFERENCE TO THE DEVELOPMENT BLOCK OF NIWALI DISTRICT, BARWANI (MP)): ‘‘राजीव गाँधी जल प्रबधंन मिषन का ग्रामीण क्षेत्रों में आर्थिक योगदान‘‘ (विकासखण्ड निवाली जिला बड़वानी (म.प्र.) के विषेष सन्दर्भ में) - Nigwale, B.S. (International Journal of Research -GRANTHAALAYAH, 2015)
Indian agriculture is the monsoon gamble and this gamble is staring at the Indian economy and the Indian public in a vacuum laid on their shoulders since time immemorial. The condition of the situation is that in the absence of water, is Indian agriculture only India's industrial businesses, factories and the entire economy stalled. Lack of water, deepening power crisis, dry fields and closed factories have affected our national product on the one hand and our international exports on the other. Consequently on the one hand supply of foreign currency shortage and on the other hand heavy financial management to deal with the current problems. "If there was no water, it would be water." Water is called "Adi Shakti", Amrit etc. in our weapons here. The whole world is incomplete without water. Water is not only a part of human body, but is a part of living images, animals and animals, and without water, all animals, trees and plants, that is, all living beings in which humans are included, will be eliminated. भारतीय कृषि मानसून का जुआं है और यह जुआं भारतीय अर्थषास्त्र और भारतीय जनता सनातन काल से अपने कंधे पर रखे हुए षून्य में ताक रही है। वस्तु स्थिति यह है कि जल के अभाव मेे भारतीय कृषि ही क्या भारत के उद्योग धंधें, कल-कारखाने, और समूची अर्थव्यवस्था ही ठप हो जाती है। पानी के अभाव में गहराता विद्युत संकट, सूखे पड़े खेत और बंद पड़े कल-कारखानों ने एक ओर हमारे राष्ट्रीय उत्पाद को प्रभावित किया है वहीं दूसरी तरफ हमारा अंतर्राष्ट्रीय निर्यात भी गड़बड़ाया है। फलतः एक ओर विदेषी मुद्रा की कमी की आपूर्ति और दूसरी ओर वर्तमान समस्याओं से निपटने के लिए भारी वित्तीय प्रबंधन। ”जल जो न होता तो ये जग जाता जल।” हमारे यहाॅँ षास्त्रों में जल को “आदि-षक्ति”, अमृत आदि कहा गया है। समस्त संसार जल के बिना अधुरा है। जल मानव षरीर का ही अंग नही अपितु जीव-जन्तु पेड़-पौधे, आदि सजीव चित्रों का एक अंग है और जल के बिना सभी जीव-जन्तु पेड़ पौधे अर्थात सभी सजीव प्राणी जिसमें मनुष्य भी षामील हैॅ समाप्त हो जायेंगें।